2017
DOI: 10.1200/jco.2017.35.15_suppl.e15733
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of second-line chemotherapy (ChT) benefit in pancreatic cancer (PC).

Abstract: e15733 Background: Second line ChT is shown to improve outcome in selected patients with PC; however there are no approved models predicting its benefit. This retrospective study was aimed to evaluate prognostic factors in patients with PC who had disease progression following 1st line ChT and their value in prediction of 2nd line ChT benefit. Methods: Records of PC patients treated in N.N. Blokhin Russian Cancer Research Center since 2000 to 2015 were analyzed. Inclusion criteria for this retrospective analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…18 Pokataev et al reported that a Karnofsky performance status of ≤70% and an NLR>5 were independent poor prognostic indicators for OS in patients with advanced pancreatic cancer receiving second-line therapy. 19 In the most comprehensive study, which included approximately 400 patients and evaluated 50 parameters, age, smoking and performance status, liver metastases, ascites, pain, jaundice, duration of firstline treatment, and type of treatment regimen were identified as independent prognostic factors for OS. 20 Age, albumin level, ALP level, ECOG PS, CEA level, and NLR level were determined as prognostic factors for OS in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…18 Pokataev et al reported that a Karnofsky performance status of ≤70% and an NLR>5 were independent poor prognostic indicators for OS in patients with advanced pancreatic cancer receiving second-line therapy. 19 In the most comprehensive study, which included approximately 400 patients and evaluated 50 parameters, age, smoking and performance status, liver metastases, ascites, pain, jaundice, duration of firstline treatment, and type of treatment regimen were identified as independent prognostic factors for OS. 20 Age, albumin level, ALP level, ECOG PS, CEA level, and NLR level were determined as prognostic factors for OS in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who received 1L FOLFIRINOX should receive gem + nab-P or gem monotherapy, those who received 1L gem + nab-P should receive either platinum-based therapy (Xelox, Gemox or OFF), irinotecan-based therapy (FOLFIRI, Nal-Iri, Nal-Iri + 5-FU-leucovorin) or uoropyrimidine, and patients who received 1L gem monotherapy should receive irinotecan monotherapy or uoropyrimidine after consideration of the condition of the patient (18). Most studies recommend 2L therapy for patients who are able to tolerate it, with a few studies describing prognostic factors for receiving and bene ting from 2L therapy (23,25,26). For example, Vienot et al (26) presented a prognostic model to predict which patients would bene t the most from 2L therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Their study found that age, smoking status, liver metastases, ECOG performance status score, jaundice, duration of 1L treatment, type of 1L regimen and pain were prognostic factors. Pokataev et al (23) provided another prognostic model to predict which patients would bene t the most from 2L chemotherapy. In their study, poor Karnofsky performance status (less than 70%) and a neutrophil-tolymphocyte ratio > 5 (NLR) were independent negative prognostic factors for a bene t of 2L therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation